Metamorphoses of individualism in Modern political philosophy - Spasenko , Natalia (Sententiae, 2000)
The author, following Niklas Luhmann, interprets the opposition "individual-society" as one of the pillars to which the ideological content of modern society is anchored. The same can be said about political philosophy: no matter how we understand the term "society" (in terms of collectivism, communalism, or holism), individualism is always understood as something ontologically rooted, as a constitutive factor of political space. Despite the resistance of influential opponents, methodological individualism has not become either a historical relic or a synonym for professional incompetence. Attempts to overcome this resistance led to the realization of a speculative tendency – self-description, which, according to Luhmann, inevitably constitutes itself as an ideology. However, individualism in the Modernity did not manifest itself as a strategy of a particular "-ology", but as a practical, non-contemplative strategy of political philosophy. The author agrees with Peter Koslowski that the question of the nature of the opposition "individual-society" can be answered only hypothetically. After all, this duality appears as: (1) a product of the historical process of individuation; (2) the result of the development of social production, the transition to private property; (3) an initial property of conditio humana. In contrast to other epochs, Modernity was the only one to propose to exclude the will to the common from individual motivations, to monistically present the individual concept of the good as a desire for personal gain.